2017
DOI: 10.3178/hrl.11.121
|View full text |Cite
|
Sign up to set email alerts
|

Bias correction of simulated storm surge height considering coastline complexity

Abstract: Abstract:In this study, we propose a new approach for model validation that can be applied to the projection of possible future storm surge heights (SSHs) on the regional scale. First, this study conducts a series of SSHs for the southeastern coast of the Korean Peninsula (KP) by six typhoons that produced SSHs over 1.0 m since 1979 and identifies the bias between simulated and observed SSHs. Next, formulas for the bias correction using a geographic parameter, in particular the coastline complexity factors, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For the rest of the domains, the bathymetric dataset with a 30-s spatial resolution (Seo 2008) was used. The time step for computation was 300 s. Yang et al (2017) verified the SuWAT model performance as hindcasting six typhooninduced SSHs 1.0 m higher around the southeastern coast of the KP. In Yang et al, by comparing the simulated maximum SSHs with the observed ones available from tidal stations, it was found that the SSHs tend to be overestimated under the following conditions: (1) the tidal station is located to the right side of the typhoon, and (2) the tidal station is close to the typhoon.…”
Section: Storm Surge Modelingmentioning
confidence: 60%
See 1 more Smart Citation
“…For the rest of the domains, the bathymetric dataset with a 30-s spatial resolution (Seo 2008) was used. The time step for computation was 300 s. Yang et al (2017) verified the SuWAT model performance as hindcasting six typhooninduced SSHs 1.0 m higher around the southeastern coast of the KP. In Yang et al, by comparing the simulated maximum SSHs with the observed ones available from tidal stations, it was found that the SSHs tend to be overestimated under the following conditions: (1) the tidal station is located to the right side of the typhoon, and (2) the tidal station is close to the typhoon.…”
Section: Storm Surge Modelingmentioning
confidence: 60%
“…It was validated that the bias correction method can improve model accuracy by 23%. However, the present study does not apply the model bias correction method proposed by Yang et al (2017), because this study considers future changes in extreme SSHs. The future changes were estimated using the difference between future projection and historical simulation.…”
Section: Storm Surge Modelingmentioning
confidence: 99%
“…The tidal elevation provides a background sea level so that the ESL probably occurs near the high position of the spring tide (Brown et al 2010, Park and Suh 2012, Choi et al 2018. The effect of the coastline geometry can cause a regional difference in ESL of more than 3 m in affected bays (Yang et al 2017, Bass et al 2018. Two typical coastline geometries, namely, a flared coastline with a convergent effect (Zhang et al 2017, He et al 2020 and an arching coastline with a lower friction (Rego and Li 2010), both attained higher ESL values at the top of the bay.…”
Section: Introductionmentioning
confidence: 99%